2006
DOI: 10.5006/1.3278281
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of the Corrosion Kinetics for Binary Nickel-Chromium Alloys under Conditions Found in Supercritical Water Oxidation Plants Processing Chlorinated Substances

Abstract: Binary Ni-Cr alloys (0 to 45 mass% Cr) were exposed to an aqueous solution resulting from the oxidation of dichloromethane (CH 2 Cl 2 ) in the presence of hydrogen peroxide (H 2 O 2 ) at 40 MPa and temperatures between ~100°C and 415°C. The composition of the reaction medium after complete oxidation of the chlorinated hydrocarbon was 0.12 m hydrochloric acid (HCl), 0.06 m oxygen (O 2 ), and 0.06 m carbon dioxide (CO 2 ). Of the alloys investigated, NiCr25 performed best in experiments for 120 h under these co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Inconel 690 has excellent corrosion resistance among the commonly used Ni–Cr alloys, because it has a higher Cr content (27–31 wt %) than the other Ni–Cr alloys, including Inconel 600, Inconel 601, and Inconel X-750 (recall Table ), This is the reason why Inconel 690 becomes the representative grade of Ni–Cr corrosion-resistant alloys and is the focus of experimental studies. Notably, NiCr25 performs best in the CH 2 Cl 2 solution at 100–415 °C and 40 MPa, other than NiCr45, with the highest Cr content among NiCr0, NiCr25, NiCr30, NiCr35, and NiCr45 . Accordingly, the influence of the Cr content on the corrosion resistance and corrosion rate of alloys with a Cr content of >30 wt % in SCW requires further discussion.…”
Section: Corrosion Characteristics Of Ni–cr Alloysmentioning
confidence: 99%
See 2 more Smart Citations
“…Inconel 690 has excellent corrosion resistance among the commonly used Ni–Cr alloys, because it has a higher Cr content (27–31 wt %) than the other Ni–Cr alloys, including Inconel 600, Inconel 601, and Inconel X-750 (recall Table ), This is the reason why Inconel 690 becomes the representative grade of Ni–Cr corrosion-resistant alloys and is the focus of experimental studies. Notably, NiCr25 performs best in the CH 2 Cl 2 solution at 100–415 °C and 40 MPa, other than NiCr45, with the highest Cr content among NiCr0, NiCr25, NiCr30, NiCr35, and NiCr45 . Accordingly, the influence of the Cr content on the corrosion resistance and corrosion rate of alloys with a Cr content of >30 wt % in SCW requires further discussion.…”
Section: Corrosion Characteristics Of Ni–cr Alloysmentioning
confidence: 99%
“…Despite having a high price, niobium exhibits the optimum corrosion resistance in SCW at 380−390 °C and 25 MPa among Inconel 625, SS 316L, Ni-20Cr, and niobium. 45 Schroer et al 46 found that NiO inhibited the dissolution of Ni-containing oxide layers, thereby effectively protecting metal from further corrosion. The corrosion behaviors of binary Ni−Cr alloys with different Cr contents in SCW indicate that the Ni−Cr alloys have the best corrosion resistance when the Cr content is ∼25 wt %.…”
Section: Comparison Of Corrosionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under the extreme conditions required, trace amounts of halogens and acids lead to extensive corrosion of many reactor materials. Extensive research efforts are managed on nickel and nickel–chromium alloys in order to overcome this technological lock 1–3. Also new concepts have been developed such as transpiring wall reactors or hydrothermal burners in which, for both of them, the corrosive species are encapsulated in a stream of pure noncorrosive water 4.…”
Section: Green Solvents In the Chemical Industrymentioning
confidence: 99%